University Students’ Acceptance of Online Learning During the Pandemic in Indonesia - Siti Yulidhar Harunasari; Retno Dwigustini; Nurhasanah Halim; Susilawati Susillawati (AL-ISHLAH: Jurnal Pendidikan, 2021)
This research aimed to investigate students’ acceptance of online learning during the pandemic by describing factors that sustain their engagement. The importance of this research is that by portraying their engagement in online learning, there would be suggestions for selecting effective strategies. A descriptive method was taken as the research method. A closed-ended e-questionnaire distributed to 263 respondents was employed in collecting data and resulted in 75% response rates. The study concluded that more than 50% of students accepted that online learning was useful, but the technology was not easy to use. Their acceptance of online learning has influenced their engagement in the online learning environment and making them quite resourceful in responding to the practice of online learning during the pandemic. The most engaging factor in sustaining students’ engagement was peer collaboration. Therefore, teamwork, peer-teaching, and peer assessment were among the main activities to sustain online learning engagement. Also, the communities of practice (CoP) could be lecturers’ first choice to sustain students’ engagement in online learning to anticipate the loss of authenticity in the learning context and trade the inexistence of concrete class, supporting facilities, and peers. The CoP could also make the learning context authentic. By implementing the two strategies, effective constructivist online learning should be achieved.